The influences on a poet and poet’s influences: Case of Nizami - Kutalmış, M. (Journal of Oriental Studies, 2024)
Nizami, who was born in 1141 in Ganja wich is situated on the territory of modern Azerbaijan and died approximately in 1204. He wrote his works in Persian although his native language was Oghuz Turkish. There was a very high civilization in Central Asian cities such as Nishabur, Merv, Khorasan, Isfahan, Farab, Otrar, Bukhara, Fergana, Samarkand, Termez, Balkh, Kashgar in ancient and medieval eras. This high civilization in Central Asia spread to the Caucasus, the Middle East, Anatolia, and Europe starting from the 9th century. Nizami trained himself very well in Ganja, which has diverse ethnicity and culture. He learned and internalized different languages, cultures, and produced many works. Nizami became a great example and a resource of inspiration for many poets and literary figures who came after him. In the era in which Nizami lived, most of the Turkic writers wrote their literary works in Persian and their scientific works in Arabic. Nizami's works have been translated into many languages. In this article, the origins of Nizami’s worldview, philosophy and poetry are examined. Key words: Nizami, Central Asia, Turkic, Persian, Philosophy, Greek Culture